Cow Urine as Emerging Biopesticides : A Mini-Review (International Journal of Scientific Research in Science and Technology, 2024)
In the current scenario, biopesticides are a topic of significant importance due to their potential to address human health and environmental issues. Loss in quality and quantity of crops due to pests is a major delinquent. To overcome this cause, farmers significantly relied on chemical pesticides, which unknowingly endured the loss of soil fertility, the presence of residue in food products and the development of resistance to pests. Consequently, the use of biopesticides was more welcomed compared to synthetic pesticides due to their substantial pest control ability and impressive versatility in controlling the development of resistance in the pests. Among the several biopesticides, botanical biopesticides demonstrate immense efficacy in controlling pests. A notable method to prepare botanical biopesticides is the combination of cow urine with medicinal plant leaf extract. This unique combination provides a better alternative to synthetic chemicals, which are expensive and cause toxic effects to the farmer, consumer, marketers, and environment. This review focuses on the various preparative methods of cow urine containing biopesticides and its potential to revolutionize agricultural pest control.